2005
DOI: 10.1016/j.joca.2005.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of sequence variations within the genes encoding collagen II, IX and XI in non-syndromic, early-onset osteoarthritis

Abstract: Early-onset OA demonstrates locus and allelic heterogeneity since the identified variations were in three different collagen genes and each of the six probands had a different mutation. It is also possible that some OA cases represent the mild end of the chondrodysplasia phenotypic spectrum. The major susceptibility alleles in this form of OA, however, remain to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 59 publications
1
48
0
2
Order By: Relevance
“…Further evidence for this conclusion is apparent in the Cho mice, which exhibit excess mineralization in the long bones (Seegmiller et al, 1971;Li et al, 1995). Sequence variations in the Col11a1 gene are also associated with osteoarthritis, early-onset osteoarthritis, degenerative lumbar spinal stenosis and cleft palate (Melkoniemi et al, 2003;Noponen-Hietala et al, 2003;Rodriguez et al, 2004;Jakkula et al, 2005). Its association with a variety of common diseases makes Col11a1 an important target for musculoskeletal disease research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further evidence for this conclusion is apparent in the Cho mice, which exhibit excess mineralization in the long bones (Seegmiller et al, 1971;Li et al, 1995). Sequence variations in the Col11a1 gene are also associated with osteoarthritis, early-onset osteoarthritis, degenerative lumbar spinal stenosis and cleft palate (Melkoniemi et al, 2003;Noponen-Hietala et al, 2003;Rodriguez et al, 2004;Jakkula et al, 2005). Its association with a variety of common diseases makes Col11a1 an important target for musculoskeletal disease research.…”
Section: Discussionmentioning
confidence: 98%
“…Type II Stickler syndrome patients have similar symptoms but are of near normal height and exhibit no bony overgrowths . Both syndromes occasionally present with cleft palate and patients frequently develop early osteoarthritis (Olsen, 1995;Snead and Yates, 1999;Rodriguez et al, 2004;Jakkula et al, 2005). Whether Marshall and Stickler syndromes are variants of the same disease or separate syndromes is controversial, but it is apparent that they are very similar and many patients display symptoms of both diseases (Winter et al, 1983;Ayme and Preus, 1984;Stratton et al, 1991;Annunen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…6 There is no convincing evidence yet that these genes are implicated in the susceptibility for primary early-onset OA occurring without dysplasia. 4,6,7 Linkage and association studies on the basis of joint-or sex-specific OA definitions have yielded several loci associated with common OA susceptibility including MATN3, 8,9 FRZB, 10 -12 IL4R, 13 ASPN 14 and CALM1. 15 Previously, we mapped a locus for early-onset osteoarthritis (familial OA, FOA) in seven families to 2q33.3 -2q34.…”
Section: Introductionmentioning
confidence: 99%
“…COL2A1 is in close physical proximity to the vitamin D receptor gene (VDR); however, a group of Dutch investigators showed that both VDR and COL2A1 influence the risk of knee OA in a manner that is not attributable to linkage disequilibrium between the 2 genes (27). Other investigators failed to identify any such association in populations in the US (28) and Finland (29).…”
mentioning
confidence: 98%